2023
DOI: 10.18632/aging.204597
|View full text |Cite
|
Sign up to set email alerts
|

Brief, weekly magnetic muscle therapy improves mobility and lean body mass in older adults: a Southeast Asia community case study

Abstract: Brief (10 min) weekly exposure to low energy pulsed electromagnetic fields (PEMFs) has been shown to improve human muscle mitochondrial bioenergetics and attenuate systemic lipotoxicity following anterior cruciate ligament surgical reconstruction. Here we present data generated from 101 participants, 62% female, aged 38-91 years, recruited from the QuantumTx Demo Centre in Singapore, wherein 87% of participants (n = 88) presented with pre-existing mobility dysfunction and 13% (n = 13) were healthy volunteers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…These adipogenic effects were clearly apparent in mice despite both white and brown adipose cells in vitro not being responsive to the same ELF-PEMF signature applied to the animal, and shown to be effective on muscle both in vitro and in vivo [ 65 , 106 ]. Studies focussed on endurance exercise agree with the results generated in response to magnetic mitohormetic strategies, demonstrating clear indices of metabolic improvement, whereas muscle mass was modestly improved [ 117 , 133 ]. Nonetheless, improvements in functional mobility were observed in a frail cohort receiving ELF-PEMF therapy, likely reflecting increases in oxidative muscular capacity, enhanced resistance to fatigue and improved metabolism [ 133 ].…”
Section: Adipogenic Consequences Of Elf-pemf Stimulationmentioning
confidence: 58%
See 2 more Smart Citations
“…These adipogenic effects were clearly apparent in mice despite both white and brown adipose cells in vitro not being responsive to the same ELF-PEMF signature applied to the animal, and shown to be effective on muscle both in vitro and in vivo [ 65 , 106 ]. Studies focussed on endurance exercise agree with the results generated in response to magnetic mitohormetic strategies, demonstrating clear indices of metabolic improvement, whereas muscle mass was modestly improved [ 117 , 133 ]. Nonetheless, improvements in functional mobility were observed in a frail cohort receiving ELF-PEMF therapy, likely reflecting increases in oxidative muscular capacity, enhanced resistance to fatigue and improved metabolism [ 133 ].…”
Section: Adipogenic Consequences Of Elf-pemf Stimulationmentioning
confidence: 58%
“…Another recent study showed significant reductions in total and visceral fat deposits in a community-based study examining an older (38–91 years of age) cohort of volunteers. Strikingly, reductions in intra-abdominal and total fat were observed after eight weeks of ELF-PEMF exposure, representing only 80 min of total exposure (10 min/week) [ 133 ]. This finding aligns with previous data showing that visceral fat is particularly prone to exercise-induced adaptive thermogenesis [ 36 , 134 ].…”
Section: Adipogenic Consequences Of Elf-pemf Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“… 153 In a study conducted by Venugobal et al, 101 participants underwent low-energy pulsed electromagnetic stimulation for 10 minutes once a week. 154 The results indicated significant improvements in mobility (timed to stand and walk, 5 sit-stand, and 4-meter walk) and body composition (increased SMM, decreased total fat mass, and reduction in visceral fat mass).…”
Section: Other Non-pharmacological Strategiesmentioning
confidence: 94%
“…These low-energy magnetic fields were shown to activate the PGC-1α (peroxisome proliferator-activated receptor-gamma coactivator (PGC)-1alpha) transcriptional pathway [ 3 , 23 , 24 ], classically associated with exercise-induced oxidative adaptations characterized by increased muscular mitochondriogenesis, enhanced systemic fatty acid oxidation, and improved insulin sensitivity [ 5 , 6 ]. Accordingly, the PEMF paradigm employed in the present study has been previously shown to produce parallel mitohormetic adaptations in cells [ 3 , 23 , 24 , 25 ], animals [ 23 ], and humans [ 26 , 27 ]. Most relevantly, as the myokine response is PGC-1α-dependent [ 5 , 6 , 24 ], it can be activated by brief PEMF exposure [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%